2012
DOI: 10.3109/10408444.2011.650789
|View full text |Cite
|
Sign up to set email alerts
|

Scientific assessment of the use of sugars as cigarette tobacco ingredients: A review of published and other publicly available studies

Abstract: Sugars, such as sucrose or invert sugar, have been used as tobacco ingredients in American-blend cigarettes to replenish the sugars lost during curing of the Burley component of the blended tobacco in order to maintain a balanced flavor. Chemical-analytical studies of the mainstream smoke of research cigarettes with various sugar application levels revealed that most of the smoke constituents determined did not show any sugar-related changes in yields (per mg nicotine), while ten constituents were found to eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
76
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(76 citation statements)
references
References 128 publications
(248 reference statements)
0
76
0
Order By: Relevance
“…In addition, acrolein is a major constituent of smoke, in particular of the gas phase of cigarette smoke, and there it accompanies a variety of further volatile TRPA1 agonists, such as formaldehyde, acetaldehyde, and crotonaldehyde (Roemer et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, acrolein is a major constituent of smoke, in particular of the gas phase of cigarette smoke, and there it accompanies a variety of further volatile TRPA1 agonists, such as formaldehyde, acetaldehyde, and crotonaldehyde (Roemer et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In no case was there a statistically significant dose relationship between inclusion level and increased severity score, even at high inclusion levels compared to the levels used in commercial cigarettes. Recently, ROEMER et al (448) published a review of scientific studies on the use of sugars as tobacco additives. The reasons for the addition of sugars in manufacturing, biological data related to sugars transferred unchanged from tobacco into mainstream smoke, and their fate during smoking and influence on smoke composition and toxicity were discussed.…”
Section: Sugarsmentioning
confidence: 99%
“…Moreover, the authors pointed out that the sweet taste and agreeable smell of caramelized sugars are appreciated in particular by starting adolescent smokers 8 . Nonetheless, Philip Morris International (PMI) researchers 14 who reviewed "publicly available studies" on the use of sugars as tobacco ingredients concluded that, although causing some differences in smoke composition (e.g. increase in formaldehyde), addition of sugars "did not lead to relevant changes in the activity in in vitro and in vivo assays" 14 (p. 244).…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, Philip Morris International (PMI) researchers 14 who reviewed "publicly available studies" on the use of sugars as tobacco ingredients concluded that, although causing some differences in smoke composition (e.g. increase in formaldehyde), addition of sugars "did not lead to relevant changes in the activity in in vitro and in vivo assays" 14 (p. 244). The industry scientists reiterate tobacco companies' claims that sugars are added to American-blend cigarettes merely to replenish sugar lost during Burley tobacco curing, and that sugar addition by no means increases the inherent risk and harm of smoking 14 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation